Dangerous Sex Offenders: Classifying, Predicting, and Evaluating Outcomes of Clinical Treatment in Bridgewater, Massachusetts, 1982-1985 - Prentky, Robert ([Verlag nicht ermittelbar], 1989)
The purpose of this data collection was to validate two classification systems, one for rapists and one for child molesters, used in a Massachusetts treatment center for sexually aggressive offenders. Rapists and child molesters were classified as two types of sex offenders and then clinically classified into subtypes based on criteria for the two taxonomies being tested. Variables include type of traffic offenses, criminal offenses, and sex offenses charged. Data on disposition of cases are also provided, along with parole and discharge information. Offenders' post-release offenses were categorized into traffic offenses, nontraffic offenses, and sex offenses.